Differences in response to antiretroviral therapy in HIV-positive patients being treated for tuberculosis in Eastern Europe, Western Europe and Latin America - Caro-Vega, Yanink; Schultze, Anna; W. Efsen, Anne Marie; Post, Frank A.; Panteleev, Alexander; Skrahin, Aliaksandr; Miro, Jose M.; Girardi, Enrico; Podlekareva, Daria N.; Lundgren, Jens D.; Sierra-Madero, Juan; Toibaro, Javier; et al. (BMC infectious diseases, 2018)
Background Efavirenz-based antiretroviral therapy (ART) regimens are preferred for treatment of adult HIV-positive patients co-infected with tuberculosis (HIV/TB). Few studies have compared outcomes among HIV/TB patients treated with efavirenz or non-efavirenz containing regimens. Methods HIV-positive patients aged ≥16 years with a diagnosis of tuberculosis recruited to the TB:HIV study between Jan 1, 2011, and Dec 31, 2013 in 19 countries in Eastern Europe (EE), Western Europe (WE), and Latin America (LA) who received ART concomitantly with TB treatment were included. Patients either received efavirenz-containing ART starting between 15 days prior to, during, or within 90 days after starting tuberculosis treatment, (efavirenz group), or other ART regimens (non-efavirenz group). Patients who started ART more than 90 days after initiation of TB treatment, or who experienced ART interruption of more than 15 days during TB treatment were excluded. We describe rates and factors associated with death, virological suppression, and loss to follow up at 12 months using univariate, multivariate Cox, and marginal structural models to compare the two groups of patients. Results Of 965 patients (647 receiving efavirenz-containing ART, and 318 a non-efavirenz regimen) 50% were from EE, 28% from WE, and 22% from LA. Among those not receiving efavirenz-containing ART, regimens mainly contained a ritonavir-boosted protease inhibitor (57%), or raltegravir (22%). At 12 months 1.4% of patients in WE had died, compared to 20% in EE: rates of virological suppression ranged from 21% in EE to 61% in WE. After adjusting for potential confounders, rates of death (adjusted Hazard Ratio; aHR, 95%CI: 1.13, 0.72–1.78), virological suppression (aHR, 95%CI: 0.97, 0.76–1.22), and loss to follow up (aHR, 95%CI: 1.17, 0.81–1.67), were similar in patients treated with efavirenz and non-efavirenz containing ART regimens. Conclusion In this large, prospective cohort, the response to ART varied significantly across geographical regions, whereas the ART regimen (efavirenz or non-efavirenz containing) did not impact on the proportion of patients who were virologically-suppressed, lost to follow up or dead at 12 months.